2011
DOI: 10.1108/03074351111153203
|View full text |Cite
|
Sign up to set email alerts
|

A brief history and recent developments in day‐of‐the‐week effect literature

Abstract: PurposeThe purpose of this paper is to provide a brief review of pre‐2003 work on the weekend effect and then discuss how recent selected work has extended our knowledge of the subject.Design/methodology/approachResults of recently published studies are organized and summarized by research question and outcomes.FindingsWhile early literature found a fairly consistent weekend effect, with positive returns on Fridays and negative returns on Mondays, more recent research shows the effect moving to other days, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…These studies are divided between those that manage to detect some kind of predictability and those, on the contrary, that reaffirm that market returns follow a random walk, that is, that it is virtually impossible to anticipate them based on stock quotations of immediately preceding periods (Famá & Bruni, 1998;Philpot & Peterson, 2011).…”
Section: Literature Reviewmentioning
confidence: 98%
See 3 more Smart Citations
“…These studies are divided between those that manage to detect some kind of predictability and those, on the contrary, that reaffirm that market returns follow a random walk, that is, that it is virtually impossible to anticipate them based on stock quotations of immediately preceding periods (Famá & Bruni, 1998;Philpot & Peterson, 2011).…”
Section: Literature Reviewmentioning
confidence: 98%
“…While many studies on returns in open markets have identified various anomalies of this kind, particularly in older series, studies that use more recent sample periods have generally indicated a lower impact or gradual disappearance of most of these effects (Philpot & Peterson, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Olowe [50] suggested the nonexistence of monthof-the-year effect in Nigerian stock market by utilizing EGARCH-in-mean model. Philpot and Peterson [51] concluded a literature review to conclude that research works pre-2003 years observed positive Friday and negative Monday returns, but research works after 2003 years observed that now this effect is reversing, vanishing or transferring to other week days. Nippani and Greenhut [47] followed Philpot and Peterson [51] and concluded that Canadian markets provided evidence for the existence of positive Friday and negative Monday returns, but after 1988, this effect reversed.…”
Section: Review Of the Literaturementioning
confidence: 99%